Structured Pharmaceutical Representative Interactions and Counterdetailing Sessions as Components of Medical Resident Education. (April 2013) - Wall, Geoffrey C.; Smith, Hayden L.; Craig, Steven R.; Yost, W. John
Introduction: Educational activities should be developed to teach residents how to constructively interact with pharmaceutical representatives and how to critically assess the provided information. Methods: An educational study was implemented during the 2010-2011 academic year in an internal medicine residency program. The study included an initial educational session on physician–industry relations and then 4 interactive sessions with the pharmaceutical representatives, each followed by a counterdetailing session provided by a clinical pharmacist. Study surveys were conducted to evaluate resident attitudes concerning pharmaceutical representative presented information before and after the counterdetailing sessions. Results: A total of 27 residents (n = 27) participated in the study. The study results revealed that residents learned new relevant product information from the representatives ( P = .002) and strongly agreed that counterdetailing was beneficial ( P = .009). Residents further agreed that they would recommend counterdetailing presentations to peers, suggested minimal changes to session formatting, and recommended its continued inclusion in their curriculum. Conclusions: This study demonstrated benefits of a comprehensive program to teach residents how to constructively interact with the pharmaceutical representatives and critically assess the information provided by the representatives. Best practices for incorporating interaction and counterdetailing sessions into medical resident curriculum should be further studied.